Sovereign Default Risk and Banks in a Monetary Union - Harald Uhlig (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper seeks to understand the interplay between banks, bank regulation, sovereign default risk and central bank guarantees in a monetary union. I assume that banks can use sovereign bonds for repurchase agreements with a common central bank, and that their sovereign partially backs up any losses, should the banks not be able to repurchase the bonds. I argue that regulators in risky countries have an incentive to allow their banks to hold home risky bonds and risk defaults, while regulators in other safe countries will impose tighter regulation. As a result, governments in risky countries get to borrow more cheaply, effectively shifting the risk of some of the potential sovereign default losses on the common central bank.
Keywords: E51; E58; E61; E62; E65; G21; G28; H63; 330; Euro zone crisis; sovereign default risk; bank regulation; risk shifting; common central bank; European Central Bank; ECB; repurchase operations; haircuts